Comment on “Evaluation of a physically based quasi-linear and a conceptually based nonlinear Muskingum methods” [J. Hydrol., 546, 437–449, 10.1016/j.jhydrol.2017.01.025] - Barati, Reza (Journal of hydrology (Amsterdam), 2017)
Perumal et al. (2017) compared the performances of the variable parameter McCarthy-Muskingum (VPMM) model of Perumal and Price (2013) and the nonlinear Muskingum (NLM) model of Gill (1978) using hypothetical inflow hydrographs in an artificial channel. As input parameters, first model needs the initial condition, upstream boundary condition, Manning’s roughness coefficient, length of the routing reach, cross-sections of the river reach and the bed slope, while the latter one requires the initial condition, upstream boundary condition and the hydrologic parameters (three parameters which can be calibrated using flood hydrographs of the upstream and downstream sections). The VPMM model was examined by available Manning’s roughness values, whereas the NLM model was tested in both calibration and validation steps. As final conclusion, Perumal et al. (2017) claimed that the NLM model should be retired from the literature of the Muskingum model. While the author’s intention is laudable, this comment examines some important issues in the subject matter of the original study.